Revision of Platycalymma Westwood, 1889, and the synonymy of Ichromantis Paulian, 1957 (Mantodea, Iridopterygidae, Tropidomantinae) - Roy, Roger; Svenson, Gavin J. (Zootaxa, 2011)
The endemic Malagasy praying mantis genus Platycalymma Westwood, 1889, is taxonomically treated with a re-description of the genus and of the type species, P. latipennis Westwood, 1889. The genus Ichromantis Paulian, 1957, is newly determined as a junior synonym to Platycalymma, which results in the inclusion of two additional species within the genus, P. befasica (Paulian, 1957) and P. dichroica (Paulian, 1957), both re-described within this study. In addition, we add three new species to the genus described from Madagascar: P. annulicornis n. sp., P. mahafalica n. sp. and P. viettei n. sp. A key to the six species in English and French is provided for increased accessibility to the people of Madagascar. Illustrations of major features used to diagnose species are provided including the head, pronotum, apex of abdomen and male genitalia. Species distribution is presented and locality coordinates are provided in print as well as being available for download as a KML file viewable in Google Earth.